MULTISPECTRAL IMAGING AS A TOOL FOR ENHANCING THE READING OF OSTRACA. (September 2014) - Sober, Barak; Faigenbaum, Shira; Beit-Arieh, Itzhaq; Finkelstein, Israel; Moinester, Murray; Piasetzky, Eli; Shaus, Arie
Abstract : A recent study shows that multispectral (MS) imaging can improve the legibility of ostraca. Several examples of Iron Age ostraca unearthed over twenty years ago in Israel (Ḥorvat ʿUza and Ḥorvat Radum) are presented, showing how new images taken with an MS system improve the reading of inscriptions that have significantly faded over time. The article provides instructions for constructing a simple and low-cost MS imaging system that yields comparable results to commercial systems. 1